Grape seed extract treatment reduces hepatic ischemia-reperfusion injury in rats - DULUNDU, ENDER; ERCAN, FERİHA; ŞENER, GÖKSEL (JOHN WILEY & SONS LTD, 2008)
This study was designed to determine the possible protective effect of grape seed extract (GSE), a widely used antioxidant dietary supplement, on hepatic ischemia/reperfusion (I/R) injury. Wistar albino rats were subjected to 45 min of hepatic ischemia, followed by a 60 min reperfusion period. GSE was administered in a dose of 50 mg/kg/day orally for 15 days before (I/R) injury and repeated before the reperfusion period. Liver samples were taken for histological examination or determination of hepatic malondialdehyde (MDA), glutathione (GSH) and myeloperoxidase (MPO) activity. Serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels were determined to assess liver functions. Lactate dehydrogenase (LDH) and cytokines (TNF-alpha and IL-1 beta) were also assayed in serum samples for the evaluation of generalized tissue damage. Ischemia/reperfusion caused a significant decrease in hepatic GSH, and significant increases in MDA level, and MPO activity. Serum AST and ALT levels, as well as LDH activity and plasma TNF-alpha and IL-1 beta levels were also elevated in the I/R group. Treatment with GSE reversed all these biochemical parameters as well as histological alterations induced by I/R. In conclusion, GSE reduced I/R-induced organ injury through its ability to balance the oxidant-antioxidant status, to inhibit neutrophil infiltration and to regulate the release of inflammatory mediators. Copyright (c) 2007 John Wiley & Sons, Ltd.
Keywords: ischemia/reperfusion; grape seed extract; lipid peroxidation; glutathione; myeloperoxidase; PROANTHOCYANIDIN EXTRACT; FREE-RADICALS; ANTIOXIDANT ACTIVITY; TISSUE-INJURY; LIVER; ISCHEMIA/REPERFUSION; TRANSPLANTATION; MECHANISMS; FLAVONOIDS; PROTECTION